Venda Online de Marcas de Moda de Luxo: Contradição de conceitos ou desenvolvimento natural do negócio da moda de luxo? - Teixeira, Sandrina Francisca (2018)
Realize whether the online sale of luxury fashion brands is a contradiction of concepts or whether it stems from a natural development of luxury fashion business is the motto of this research. The present work deals with the problems associated with the E-commerce Strategies of Luxury Fashion Brands, in the way brands generate the apparent contradiction between the characteristics of online sales and the attributes of luxury fashion. It uses content analysis of luxury brand websites to identify and evaluate how brands approach the market in an omnichannel perspective and how they build a luxurious online environment achieving a Luxemosphere and enabling an online experience with the brand, compatible with its luxury status. The conclusions indicate an increase in the adoption of e-commerce by the luxury fashion brands of the sample, but with different execution profiles and, identifying needs for improvement, namely in the presentation of products and the construction of omnichannel.